"Use of a GIS-Based Multicriteria Decision-Making Approach, to Increase Accuracy in Determining Soil Suitability", Iran. Issue 5 (9th March 2023) - Akhavan, Sahar; Jalalian, Ahmad; Toomanian, Norair; Honarjo, Naser
ABSTRACT: Land suitability analysis and land use mapping are one of the most practical applications of Geographic Information Systems in land resource management. In the present study, the qualitative assessment of land suitability was investigated using fuzzy and parametric hierarchical analysis process models for the irrigated wheat crop. Soil characteristics, climatic conditions, topography, and accessibility were selected based on the Food and Agriculture Organization framework and expert opinions. The interpolation function was used to plot values to points in terms of quality/terrain characteristics for the type of operation and the evaluation was performed based on parametric and fuzzy analytical hierarchy process models. According to the parametric model, the values of land indices vary from 50% in some places to 78% in the study area, which classifies the plain from suitable classes (S2) to upper classes (S1). Preferred values fuzzy analytical hierarchy process for wheat cultivation in the study area are from 0.25 to 0.73, which is classified as medium to very high for wheat production. Kappa Cohen coefficient between parametric land indices and preferential values fuzzy analytical hierarchy process with observed wheat yield varies between 0.03 and 0.237, respectively, which confirms the validity of both models in estimating land suitability for irrigated wheat production in the study area. The results of the present study show that fuzzy analytical hierarchy process is an effective strategy to increase the weight accuracy of the criteria affecting the analysis of land suitability.